A theropod and sauropod track assemblage from the Lower Jurassic of Guizhou, China. (2nd September 2021) - Xing, Lida; Lockley, Martin G.; Klein, Hendrik; Zeng, Rong; Peng, Guangzhao; Ye, Yong; Hao, Baoqiao; Persons, W. Scott
ABSTRACT: The newly discovered Maoshajing tracksite in the Lower Jurassic Longtoushan Group of Guizhou Province, China is dominated by well-preserved medium-sized theropod tracks of the Grallator-Eubrontes plexus type, and associated with a few sauropod tracks. This saurischian dominated ichnofauna is typical of the Lower Jurassic biochron of China and elsewhere. It is also consistent with the sparse body fossil record, making it a type 2a deposit in which tracks are more abundant, and therefore also more important in providing a useful census of the tetrapod fauna. It is argued that small tracksite surfaces are more useful in 'capturing' (registering) evidence of small and potentially more active theropod movements than the activity of larger saurischians (sauropodomorphs) which may have been less abundant and less active in areas of any given size.